First record of a fossil larva of Hemerobiidae (Neuroptera) from Baltic amber - Makarkin, Vladimir N.; Wedmann, Sonja; Weiterschan, Thomas (Zootaxa, 2012)
A fossil larva of Hemerobiidae (Neuroptera) is recorded for the first time from Baltic amber. The subfamilial and generic affinities of this larva are discussed. It is assumed that it may belong to Prolachlanius resinatus, the most common hemerobiid species from the Eocene Baltic amber forest. An updated list of extant species of Hemerobiidae with described larvae is provided.